On the use of troglomorphic characters in Namanereidinae (Annelida; Nereididae) systematics - Alves, Paulo Ricardo; Glasby, Christopher J.; Santos, Cinthya Simone Gomes (Zootaxa, 2018)
The Namanereidinae are one of the most successful polychaete groups to colonize subterranean waters. Many species have evolved adaptations to underground life including elongation of appendages and reduction of eyes and pigmentation. However, the use of these troglomorphic characters in the group’s systematics is contentious. The present study conducts a series of tree searching and phylogeny reconstructions to evaluate the influence of these characters in the phylogeny of the group. Results show that troglomorphic characters cause no serious errors in the phylogenetic reconstruction of Namanereidinae, and support the two existing genera, which can be unequivocally distinguished by non-troglomorphic traits. As a consequence of this phylogenetic hypothesis the following taxonomic changes are required: Lycastoides becomes a junior synonym of Namanereis, and its only species becomes a new combination, N. alticola n. comb. and Namalycastis occulta is moved to Namanereis becoming Namanereis occulta n. comb.